المعايير الخاصة بحوكمة المصارف الإسلامية دراسة تطبيقية على المصارف الإسلامية القطرية = Special standards corporate governance of Islamic banks: an applied study on Islamic banks in Qatar - Ali Muhyiddin, Asma'a; Arif, Arif Ali; Hasan, Aznan; Ali Ahmad, Abdullah (IIUM Press, International Islamic University Malaysia, 2020)
هدفت هذه الدراسة لدراسة المتطلبات الخاصة لحوكمة البنوك الإسلامية، من خلال توضيح مفهوم الحوكمة وإطارها التشريعي والتاريخي، وأبرز السلطات الرقابية والإشرافية العالمية والإسلامية التي اهتمت وأصدرت معايير للحوكمة سواء كانت خاصة بالمصارف أو عامة لكل المؤسسات، ثم ناقشت المتطلبات الخاصة لحوكمة المصارف الإسلامية لدى السلطات الرقابية والإشرافية الإسلامية والقطرية، ومدى تطبيق المصارف الإسلامية القطرية لها، وخلصت الدراسة إلى أن المصارف الإسلامية القطرية تحقق المتطلبات الإضافية لحوكمة المصارف الإسلامية، واتبعت الباحثة منهجين أساسين: المنهج الاستقرائي؛ لجمع المعلومات ذات الصلة بالدراسة، والمنهج التحليلي من خلال مقارنة تقارير الحوكمة في المصارف الإسلامية القطرية مع المتطلبات الإضافية لحوكمة المصارف الإسلامية في تعليمات مصرف قطر المركزي، وإلقاء الضوء على تطبيقات المصارف الإسلامية لتلك التعليمات. ******************************************************************************** The aim of this study is to discuss the specific requirements for the corporate governance of Islamic banks by clarifying the concept of governance and its legislative and historical framework, and the most prominent supervisory and supervisory authorities in the world and Islamic countries, which focused on and issued standards for governance, whether private banks or general for all institutions. Islamic and Qatari banks and the extent to which Qatari Islamic banks have applied them. The study concluded that Qatari Islamic banks are achieving the additional requirements for Islamic banking governance. The researcher used the descriptive analytical method to addressing the main principals which relevant to this study. The analytical approach was also used to analyzed the corporate governance reports in Islamic banks in Qatar and compare it with corporate governance standards in Central Qatar Bank